Pengaruh Recruitment Source dan Job Seeker's Perception terhadap JOb Seeker's Intention to Pursue the Job di Kompas Gramedia Group - Tommy Budiman; Nurina Putri Handayani (Universitas Multimedia Nusantara, 2016)
Job seeker's intention to pursue the job is to be considered by a company in order to attract a job applicant. The existence of an employee wishes to pursue a job (job seeker's intention to pursue the job) thought to be affected by a job applicant easily obtain employment information from a variety of existing media (recruitment sources). In addition, the perception of a job applicant (job seeker's perception) against a company is also thought to influence the decision to pursue such work. The purpose of this study was to determine the influence of recruitment sources and job seeker's perception of job seeker's intention to pursue the job in Kompas Gramedia Group. In this study, questionnaires done by using non-probability sampling of 100 respondents who are a job applicant that have or are applying for a job at one of the subsidiaries of Kompas Gramedia Group, domiciled in Tangerang. Data collection methods used in this research by distributing questionnaires. Meanwhile, the research method used is quantitative and descriptive research methods. The results showed that the newspaper has no effect and no significant effect on job seeker's intention to pursue the job in Kompas Gramedia Group. Internet and friends / relatives have positive and significant effect on job seeker's intention to pursue the job in Kompas Gramedia Group. In addition, person - organization fit and organizational culture have positive and significant impact on the job seeker's intention to pursue the job. And based on the results of this research, it is known that the recruitment sources (newspaper, internet, and friends / relatives) as well as the job seeker's perception (person - organization fit and organizational culture) can explain and affect job seekers intention to pursue the job in Kompas Gramedia Group amounted to 46.8 %. Keywords: recruitment source, job seeker’s